Status and Challenges of Medical Waste Management in Hospitals of Iran - Eslami, Akbar; Nowrouz, Parviz; Sheikholeslami, Samira (Civil Engineering Journal, 2017)
Medical waste is of great importance due to its hazardous nature that can cause undesirable effects on humans and the environment. This study focuses on medical waste management in hospitals of Iran. Data were collected based on questionnaires and for self-report of medical waste management. The results along with other information were sent to the ministry of health network system. Results indicated that the mean generation rate of non-hazardous and sharp and infectious and total wastes in Iran were, respectively, 1.84, 1.09 (36.9% of total waste generated) and 2.98 kg/bed/day. Chemical waste generation rate in Iran is 0.02 kg/bed/day (0.68%) that relative to infectious waste and total waste generation rate is much lower which could be due to improper segregation of medical wastes. There is significant differences between private and governmental hospitals, in terms of infectious and sharp waste generation rates (P=0.027). Also there are significant differences between specialized and general hospitals in group of non-hazardous waste (P=0.039), infectious waste (P=0.001) and total waste generation rate (P=0.02). 65.41% of governmental hospitals used autoclave for infectious waste treatment. In the private and governmental hospitals 14.8% and 24.29%, respectively not have any treatment devices and hazardous waste was disposed without treatment.